The Importance of Maintaining the Neutrality of State Civil Apparatus Based on the Values of the Malay Culture - Rafi, M.; Suswanta, Suswanta; Wicaksono, Baskoro (Jurnal Ilmiah Peuradeun, 2021)
This article described the various phenomena of violations by the State Civil Apparatus in the momentum of the democratic party in Indonesia and aimed to determine the extent to which Malay Cultural Values ​​can maintain the neutrality of the State Civil Apparatus. This study used an exploration-oriented literature review method. Then, data were obtained through documentation techniques by reviewing and exploring several journals, books, and other related documents. To analyze the data, the content analysis method was used to get valid conclusions based on the context. The results showed that some Malay cultural values ​​that must be possessed by the State Civil Apparatus were the principles of honesty, justice and truth, hard work and perseverance, shame, and compassion. All the principles taught can maintain the neutrality of the State Civil Apparatus if each individual has high awareness and commitment to do so. Thus, the values ​​taught by the Malay Culture have an essential meaning in maintaining the neutrality of the State Civil Apparatus.